ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL SPLDV BERDASARKAN TEORI NEWMAN DI KELAS VIII - Chofifa Indah E. Mamonto; Rosiah J. Pulukadang; Ontang Manurung (ADIBA : JOURNAL OF EDUCATION, 2022)
A system of two-variable linear equations (SPLDV) is a system or entity of several similar two-variable linear equations. This study aims to determine student errors in completing the Newman Theory Two-variable Linear Equation System material. The method used is a descriptive method with a qualitative approach. Of the 5 questions given, 2 numbers were answered correctly, namely number 2 and number 5. In this study, 5 respondents were selected who made mistakes in solving the two-variable system of equations to be interviewed about the questions that had been given. Of the five types of student errors according to Newman's Theory in solving system problems of linear equations, two errors that often occur are errors in writing the final answer with a percentage of 49%, then process skill errors with a percentage of 47%, errors in understanding questions with a percentage of 32%, reading error with a percentage of 13% and the last transformation error with a percentage of 10%.